2016
DOI: 10.1177/0284185116649797
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nodule characteristics on sampling number and duration of thyroid fine-needle aspiration biopsy: size does not matter, but cystic degeneration ratio does

Abstract: Background Ultrasound-guided fine needle aspiration biopsy (FNAB) of thyroid nodules, though the most accurate method to rule out malignancy, still has an inherent risk of yielding non-diagnostic specimens despite immediate assessment of specimen adequacy by an on-site cytopathologist. Purpose To evaluate the effects of nodule volume and extent of cystic degeneration on total biopsy time and number of aspirations required for obtaining an adequate specimen. Material and Methods A total of 510 patients underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
8
1
Order By: Relevance
“…Another research study also indicated that partially cystic nodules had higher elasticity modules than solid ones in both shear wave elastography (SWE) and strain elastography although the cause remains unknown (16,17). In addition, it was reported by Cengic et al (18) that the success rate of fine-needle aspiration (FNA) was lower and total biopsy time of FNA was longer in predominantly cystic nodules than that in predominantly solid ones. Furthermore, Gu et al (19) and Chan et al (20) reported that the risk of being malignant in solid or predominantly solid thyroid nodules was higher than that in the cystic or predominantly cystic nodules.…”
Section: Discussionmentioning
confidence: 97%
“…Another research study also indicated that partially cystic nodules had higher elasticity modules than solid ones in both shear wave elastography (SWE) and strain elastography although the cause remains unknown (16,17). In addition, it was reported by Cengic et al (18) that the success rate of fine-needle aspiration (FNA) was lower and total biopsy time of FNA was longer in predominantly cystic nodules than that in predominantly solid ones. Furthermore, Gu et al (19) and Chan et al (20) reported that the risk of being malignant in solid or predominantly solid thyroid nodules was higher than that in the cystic or predominantly cystic nodules.…”
Section: Discussionmentioning
confidence: 97%
“…The effect of various factors on the adequacy of US‐guided thyroid FNA has been investigated broadly in the past few years. Some studies suggest that the experience of the operator plays a significant role while other studies discuss the impact of nodule characteristics, sampling technique, needle size, and on‐site evaluation 7‐11 . In our study, to further investigate the impact of nodule size and composition, we removed the effect of potential confounding factors including the operator experience, needle size, sample preparation, and adequacy assessment by analyzing FNAs performed by a single experienced radiologist using a 25‐G needle, on‐site adequacy assessments performed by an experienced cytopathologist or cytopathology fellow, and slide preparation performed by a cytotechnologist or cytopathology fellow.…”
Section: Discussionmentioning
confidence: 99%
“…Also, lesions with a cystic component may require more sampling to achieve sufficient yield. 125 Further, molecular heterogeneity, such as intratumor mutational heterogeneity, may be present even when cytologic appearances with light microscopy are relatively homogenous.…”
Section: Lesion Heterogeneitymentioning
confidence: 99%